Comparison of Histological Characteristics of Acellular Dermal Matrix Capsules to Surrounding Breast Capsules in Acellular Dermal Matrix–Assisted Breast Reconstruction. Issue 5 (May 2016) - Yu, Deborah; Hanna, Kasandra R.; LeGallo, Robin D.; Drake, David B.
Abstract : Introduction: Despite the widespread adaptation of acellular dermal matrix (ADM) to breast reconstruction, we are just now exploring how these materials integrate and perform in vivo. The goal of this study was to compare the histological characteristics between expander capsules to an area without the ADM. Methods: Women undergoing implant-based breast reconstruction at the University of Virginia Health System using a decellularized regenerative dermal matrix were enrolled in this prospective, evaluator-blinded, institutional review board–approved study. Twenty-four non-ADM and 24 ADM breast capsule biopsy specimens were collected from 15 women and analyzed for the histological parameters of inflammation, vascular proliferation, capsule fibrosis, foreign body giant cell inflammatory reaction, and myofibroblasts using a previously described semiquantitative scoring system. The pathologist evaluating the specimens was blinded to the tissue source and biopsy location. Results: There was significantly less inflammation and fewer myofibroblasts in the ADM capsule biopsy samples compared with the no-ADM capsule biopsy samples (inflammation: ADM, 0.83; no-ADM, 1.83; P = 0.001; myofibroblasts: ADM, 0.79; no-ADM, 1.46; P = 0.024). Significantly less vascular proliferation in the ADM samples was seen compared with the no-ADM samples (ADM, 0.75; no-ADM, 1.42; P = 0.036). No statistical difference in the presence of an inflammatory capsule was observed in the no-ADM biopsy samples compared with the ADM capsule biopsy samples ( P = 0.060). Conclusions: When used for staged breast reconstruction, this unique, sterile ADM seems to induce less inflammation. Moreover, the significantly decreased presence of myofibroblasts in this material supports the observed clinical findings of decreased capsular contracture in ADM-assisted breast reconstruction.